Direct‐Push Color Logging Images Spatial Heterogeneity of Organic Carbon in Floodplain Sediments. Issue 12 (10th December 2020) - Klingler, Stefan; Cirpka, Olaf A.; Werban, Ulrike; Leven, Carsten; Dietrich, Peter
Abstract: In soils and sediments, large amounts of total organic carbon (TOC) mark reducing conditions. As dark sediment colors are good predictors for high‐TOC zones, they indicate hot spots of biogeochemical turnover and microbial activity. Traditionally, obtaining the sediment color or TOC at depth requires costly core sampling, resulting in poor horizontal resolution and related uncertainty caused by interpolation. We suggest using a direct‐push tool for optical screening of the sediment color to acquire multiple high‐resolution vertical color profiles and demonstrate its applicability to a biogeochemical transition zone in floodplain sediments, dominated by tufa. We use Gaussian mixture models for a cluster analysis of 35 color logs in the International Commission on Illumination (CIE) L * a * b * color space to identify three colorfacies that differ in lithology and TOC content: a dark colorfacies that agrees well with peat layers, a gray colorfacies associated with clay, and a creamy‐brown facies made of autochthonous carbonate precipitates. We test different approaches either to infer the TOC content from color metrics, namely, the lightness and chroma, across all facies, or to identify TOC ranges for each colorfacies. Given the high variability in TOC due to organic carbon specks in the tufa, the latter approach appears more realistic. In our application we map the 3‐D distribution of organic matter in a floodplain in distinct facies over 20, 000 m 2 down to 12 m depth. While we relate the sediment color only to the TOC content, direct‐push color logging may also be used for in situ mapping of other biogeochemically relevant properties, such as the ferric‐iron content or sedimentary structure. Plain Language Summary: Geologists can say a lot about soils and loose materials in the ground by looking at their color. Dark materials normally contain dead plants, called organic carbon, which are food for bacteria and cause chemical reactions. To get the color of the soil, geologists normally need soil samples, but getting them from depth takes time and money. We test a method of pushing a camera into the ground and recording the color therein. From the recorded color we can say which type of geological material is at which depth and how much organic carbon is there without taking samples everywhere. This can be done very quickly, so that we can do it over a large area and down to the depth of the loose material in the ground, where most of the groundwater flows. Key Points: Direct‐push methods allow vertical in situ profiling of sediment color at high resolution Cluster analysis reproducibly delineates colorfacies indicative of sedimentary units Site‐specific relationships between color and TOC in sediments permit identifying biogeochemical hot spots